Electrochemical corrosion resistance of aluminum alloy 6101 with cerium-based coatings in an alkaline environment - Khan, Ahsan Riaz; Zhang, Hai-Jun; Jun, Zhang; Eldin, Sayed M; Alsaiari, Norah Saleem; Katubi, Khadijah Mohammedsaleh (Frontiers in Chemistry, 2022)
Chromium free materials as eco-friendly coatings with higher corrosion resistance are crucial in various industrial processes. Herein, we report the deposition of cerium-based conversion, a chromium-free, eco-friendly chemical conversion coating for aluminum alloy 6101 by the dip coating method. Immersion in cerium salt precursors assisted with hydrogen peroxide were formed in the deposition of cerium-based conversion coatings on aluminum alloy 6101 under different bathing temperature. The electrochemical corrosion behavior has been assessed in alkaline solution of sodium hydroxide (pH 11), including mass loss measurements, free corrosion risk, polarization, and electrochemical impedance spectroscopy. X-ray diffraction and photoelectron spectroscopy analysis showed that the coatings were composed of Ce (III) and Ce (IV) oxides. Surface modifications and surface degradation of the coating and substrate after the immersing into corrosive media was analyzed by the scanning electron microscopy. Additionally, energy dispersive scanning (EDS) analysis demonstrates the elemental composition before and after corrosion of the cerium salt conversion-based coating. The results demonstrate that selectively deposited cerium-based conversion coatings can improve the corrosion resistance up to 96% in a strong corrosive alkaline media.